Novel 2,4-dimethyl-5-((E)-3-phenyl-3-oxoprop-1-enyl)-1H-pyrrole-3-carboxylic acid derivatives: new leads in cancer and bacterial chemotherapy - Rasal, Nishant K.; Sonawane, Rahul B.; Choudhari, Amit S.; Chakraborty, Shakti S.; Sarkar, Dhiman D.; Jagtap, Sangeeta, V. (ChemistrySelect, 2018)
The efficiently designed and synthesized novel 2,4-dimethyl-5-((E)-3-phenyl-3-oxoprop-1-enyl)-1H-pyrrole-3-carboxylic acid derivatives has been described here which is encouraged by the anticancer activities associated with sunitinib and semaxanib. Synthesized compounds were characterized by (HNMR)-H-1, (CNMR)-C-13 and high-resolution mass spectrometry (HRMS). They are evaluated for invitro antiproliferative properties on cancer cell lines as well as antibacterial activity against gram-positive and gram-negative species. The bioassay results revealed that several compounds exhibit potential antiproliferation activity. Among them, the lead compound 2,2,2-trifluoroethyl 5-((E)-3-(3-fluoro-4-(trifluoromethyl)phenyl)-3-oxoprop-1-enyl)-2,4-dimethyl-1H-pyrrole-3-carboxylate (9g) showed the most potent anticancer activity against MDA-MB-231 and PC-3 cancer cell line with GI(50) values of 5.51 and 5.15 mu g/mL and subsequently more active than sunitinib (GI(50): 6.50 mu g/mL) against PC-3. Same compound 9g also exhibits the most potent antibacterial activity against gram-positive bacteria Bacillus subtilis and Staphylococcus aureus with IC50 of 1.44 and 1.54 mu g/mL. In silico prediction, shows that all seven potent compounds obeyed Lipinski rule for druglikeness. Structure-activity relationship (SAR) study reflect the activity enhance with electron withdrawing group on aryl ring and replacement of acid by its bioisosteres i.e. amide and ester group. These studies have successfully identified many newly synthesized compounds as potential anticancer as well as antibacterial agent for further development.